Monoclonal antibodies produced against sporozoites of the human parasite Plasmodium malariae abolish infectivity of sporozoites of the simian parasite Plasmodium brasilianum. - Cochrane, A H (1985)
We have used a sporozoite neutralization assay to define the biological relevance of the cross-reactivity of two monoclonal antibodies, raised against sporozoites of the human parasite Plasmodium malariae (Uganda 1/CDC), with sporozoites of the simian parasite Plasmodium brasilianum (Colombian). In vitro incubation of each of these two monoclonal antibodies with sporozoites of P. brasilianum totally abolished the infectivity of these parasites for Saimiri sciureus. Using Western blot analysis and one of the P. malariae monoclonal antibodies, we identified two sporozoite proteins characteristic of the Colombian isolate of P. brasilianum with apparent molecular weights of 56,000 and 66,000. The same monoclonal antibody identified two proteins in an extract of the Peruvian isolate of P. brasilianum with apparent molecular weights of 59,000 and 69,000.